Barium titanate-based leadless piezoelectric ceramic material as well as preparation method and application thereof

By introducing Sn ions into BT lead-free piezoelectric ceramics, a multiphase structure and polar snow mud domain structure are formed, the problem of difficult balance between electrical and mechanical properties of existing materials is solved, and a number of excellent performances are achieved. It is suitable for the new generation of high-precision super-intelligent devices.

CN119569446AInactive Publication Date: 2025-03-07CHENGDU UNIV

Patent Information

Application Number
CN202411764155.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to balance the existing piezoelectric ceramic materials between electrical and mechanical properties, especially the piezoelectric coefficient d33 of pure BT lead-free piezoelectric ceramics is small and the mechanical properties are insufficient, which limits its wide application in the electronic industry.

Method used

By introducing Sn ions into BT lead-free piezoelectric ceramics, its concentration is regulated to form a multiphase structure with flat free energy, and induced polar snow mud domain structure, thereby showing excellent kinetic characteristics under the action of the external field, while improving piezoelectric properties, electrostrictive properties, electrical card properties and mechanical properties.

Benefits of technology

The BT-based lead-free piezoelectric ceramics have achieved a combination of excellent electrical properties and ultra-high mechanical properties, which are specifically manifested as the piezoelectric coefficient d33 reaches 820pC/N, the electrostrictive performance Q33 = 0.045m4/C2, the low-electric field near-room temperature electric card has excellent performance, and the mechanical hardness HV = 6.15GPa, which is far beyond the performance of pure BT lead-free piezoelectric ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119569446A_ABST
    Figure CN119569446A_ABST
Patent Text Reader

Abstract

The invention discloses a barium titanate-based leadless piezoelectric ceramic material and a preparation method and application thereof, and relates to the technical field of functional materials, the chemical formula of the barium titanate-based leadless piezoelectric ceramic material is Ba0. 9Sr0. 1Ti1-xSnxO3, x = 0-0.10, and x represents a mole fraction. By regulating and controlling the concentration of Sn ions in the BT-based lead-free piezoelectric ceramic, a multiphase structure with flat free energy is formed near the room temperature, meanwhile, an unconventional short-range disorderly-arranged polar snow-mud-state domain structure is induced, an extremely good domain change dynamic behavior is shown under the action of an external field, and the piezoelectric ceramic is prepared. Meanwhile, excellent piezoelectric property, electrostrictive property, electrocaloric property and mechanical property are obtained, and a candidate material is provided for a new generation of multifunctional high-precision electronic information devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional materials, and in particular to a barium titanate-based lead-free piezoelectric ceramic material and a preparation method and application thereof. Background Art

[0002] Piezoelectric ceramics are advanced functional materials that can realize the mutual conversion of mechanical energy and electrical energy. They are currently widely used in various fields such as force, light, sound, electricity, and medicine. In the past, lead-based piezoelectric ceramics were widely used due to their excellent mechanical and electrical properties and good temperature stability. However, the main raw material of lead-based piezoelectric ceramics is lead oxide (accounting for about 70% of the total mass of the raw materials), which can cause harm to human health and the ecological environment during production and use. As people's awareness of their own health, ecological environmental protection, and social sustainable development strategies increases, a series of lead-free piezoelectric ceramics designed to replace lead-based piezoelectric ceramics have attracted people's attention, such as barium titanate (BaTiO3, BT), bismuth ferrite (BiFeO3, BFO), bismuth titanate (Bi4Ti3O 12 , BIT), potassium sodium niobate (Na 0.5 K 0.5 NbO3, KNN), etc. In addition, the EU updated the Restriction of Hazardous Substances (RoHS) legislation in 2016, which greatly limited the lead content in electronic components and further stimulated the development of lead-free piezoelectric ceramic materials in the entire industrial field.

[0003] Barium titanate (BT) ceramics are typical ABO3 perovskite structure piezoelectric materials and the earliest discovered lead-free piezoelectric ceramic materials. Because of its high dielectric properties, large electromechanical properties and good piezoelectric properties, it has always been a hot research topic in the scientific and industrial communities. However, the piezoelectric coefficient d of pure BT piezoelectric ceramics is 33 It is relatively small, only 190pC / N, which is not conducive to its large-scale application in the field of electronics industry. With the development of synthesis technology, such as microwave sintering, hot pressing sintering, template grain growth, etc., the piezoelectric properties of BT lead-free piezoelectric ceramics have been further improved. Most importantly, through chemical doping, BT lead-free piezoelectric ceramics can undergo controllable structural phase transition, resulting in higher piezoelectric activity and obtaining a higher piezoelectric coefficient (d 33 >400pC / N). The excellent piezoelectric properties enable BT lead-free piezoelectric ceramics to be better used in electronic devices such as sensors and transducers, and bring huge economic benefits. In addition to piezoelectric behavior, the construction of multiphase boundaries through doping strategies has also accelerated the development of other electrical properties of BT lead-free piezoelectric ceramics. For example, strontium (Sr)-doped BT lead-free piezoelectric ceramics can obtain high strain and small ferroelectric hysteresis (H hyst <2%), showing excellent electrostrictive properties (Q 33 =0.03M 4 / C2 ). The introduction of Sr into BT lead-free piezoelectric ceramics can also adjust the ferroelectric-paraelectric transition temperature to near room temperature, greatly improving the electrocaloric performance of BT lead-free piezoelectric ceramics (ΔT = 0.42K, ΔE = 20kV / cm). The addition of niobium (Nb) into BT lead-free piezoelectric ceramics is beneficial to further reduce the phase transition temperature and enhance the dispersion behavior, and obtain electrocaloric performance in a wider operating temperature range near room temperature (ΔT max >50%).

[0004] With the increasing development of science and technology, the scientific and industrial communities are paying more and more attention to how to balance the development of various electrical properties or obtain multiple excellent electrical properties in the same BT piezoelectric ceramics to meet the needs of the new generation of advanced multifunctional devices towards super-intelligent development and obtain huge social and economic benefits. For example, in BT-based piezoelectric devices, the functions of monitoring vibration, displacement control, energy conversion, and discharging the heat generated by the machine (refrigeration) can be realized at the same time, which not only saves piezoelectric materials, but also makes piezoelectric devices more intelligent or super-intelligent, which is incomparable to traditional single-function piezoelectric devices.

[0005] Studies have shown that rare earth cerium (Ce) can effectively regulate the ferroelectric-paraelectric phase transition of BT piezoelectric ceramics, and can simultaneously obtain high electrostrictive strain and electrocaloric performance at a high electric field of 60kV / cm. Nb ions also help to establish crossover regions across multiple ferroelectric phases in BT lead-free piezoelectric ceramics, thereby obtaining large electrostrictive strain and excellent energy storage performance at a high electric field of 80kV / cm.

[0006] Although doped and modified BT piezoelectric ceramics show great application potential in the emerging field of advanced intelligent functional devices, so far, there are few studies on the balanced development or simultaneous enhancement of multiple electrical properties in the same BT piezoelectric ceramic system. In addition, the mechanical properties of piezoelectric ceramics restrict the output stability and reliability of piezoelectric devices. Compared with electrical properties, the research on the mechanical properties of piezoelectric ceramic materials is very lacking, which is not conducive to the optimization design of their stability and reliability. Therefore, the development of a new generation of BT lead-free piezoelectric ceramic materials that have both multiple excellent electrical properties and ultra-high mechanical properties will be an important task for the development of intelligent electronic information technology and human progress in the new era. Summary of the invention

[0007] Based on the current problems of single electrical functionality and low mechanical properties of piezoelectric ceramics, the purpose of the present invention is to provide a barium titanate-based lead-free piezoelectric ceramic material and its preparation method and application. By regulating the concentration of Sn ions in BT-based lead-free piezoelectric ceramics, a multiphase structure with flat free energy is formed near room temperature, and at the same time, an unconventional short-range disordered polar slush domain structure is induced. Under the action of an external field, it exhibits excellent domain change dynamic behavior, and simultaneously obtains excellent piezoelectric properties, electrostrictive properties, electrocaloric properties and mechanical properties, providing candidate materials for a new generation of high-precision ultra-intelligent electronic information devices or other new intelligent electronic industries that integrate multiple functions.

[0008] The present invention is achieved through the following technical solutions:

[0009] In a first aspect, the present application provides a barium titanate-based lead-free piezoelectric ceramic material, wherein the chemical formula of the barium titanate-based lead-free piezoelectric ceramic material is Ba 0.9 Sr 0.1 Ti 1-x Sn x O3, wherein x=0-0.10, x represents the mole fraction. Specifically, x can be 0.00 or 0.02 or 0.04 or 0.06 or 0.08 or 0.10.

[0010] The present invention adopts the "ion doping strategy" to first introduce Sr ions to replace the A-site Ba ions in the ABO3 structure in the BT lead-free piezoelectric ceramics, and then introduce Sn ions to replace the B-site Ti ions in the ABO3 structure to synthesize a new BT-based lead-free piezoelectric ceramic material system: Ba 0.9 Sr 0.1 Ti 1-x Sn x O3(BSTS x , 0≤x≤0.1). The invention aims to form a multiphase structure with flat free energy near room temperature by regulating the concentration of Sn ions in BT-based lead-free piezoelectric ceramics, and at the same time induce an unconventional short-range disordered polar slush domain structure, which exhibits excellent domain change dynamics under the action of an external field, and simultaneously obtains excellent piezoelectric properties, electrostrictive properties, electrocaloric properties and mechanical properties, providing candidate materials for a new generation of high-precision electronic information devices with multifunctionality. Among them, when the concentration of Sn ions is x=0.08, the BT-based lead-free piezoelectric ceramics simultaneously obtain excellent piezoelectric properties d 33 =820pC / N, excellent hysteresis-scaling performance Q 33 =0.045m 4 / C 2 , excellent near-room temperature electrocaloric performance under small electric field (ΔT=0.822K, ΔT / ΔE=0.425K·mm / kV) and ultra-high mechanical properties (HV =6.15GPa). These performance indicators far exceed the electrical and mechanical properties of pure BT lead-free piezoelectric ceramics, and are also better than other multifunctional BT-based lead-free piezoelectric ceramic materials reported so far. The BT-based lead-free piezoelectric ceramics of the present invention have both excellent electrical properties and ultra-high mechanical properties, and are expected to be applied to a new generation of high-precision ultra-intelligent devices with multifunctionality or other new intelligent electronic industries, making important contributions to the development of electronic information intelligent technology and human progress in the new era.

[0011] In a second aspect, the present application provides a method for preparing a barium titanate-based lead-free piezoelectric ceramic material, comprising the following steps:

[0012] (1) weighing chemical reagents BaCO3, TiO2, SrCO3 and SnO2 according to the chemical formula of barium titanate-based lead-free piezoelectric ceramic materials to prepare powder;

[0013] (2) using the powder to perform granulation molding to prepare a disc body;

[0014] (3) performing a debinding process on the disc blank;

[0015] (4) sintering the debinding disc green body to obtain a disc ceramic material;

[0016] (5) The sintered disc ceramic material is subjected to silver plating and polarization treatment to obtain a lead-free piezoelectric ceramic material.

[0017] Furthermore, when preparing the powder in step (1), the weighed chemical reagents are firstly subjected to ball milling treatment, then subjected to drying treatment, and finally subjected to pre-calcination treatment.

[0018] Furthermore, the temperature during the pre-firing treatment is controlled at 1160° C. to 1220° C., and the temperature is kept at 120 min to 180 min.

[0019] Furthermore, when preparing the disc body in step (2), the pre-burned powder is first ground and then added to a polyvinyl alcohol binder for grinding and granulation. The granulated powder is loaded into a mold and formed on a powder dry pressing machine.

[0020] Furthermore, the prepared disc blank has a diameter of 10 mm and a height of 0.8 mm to 1.5 mm.

[0021] Furthermore, the formed disc blank contains a large amount of PVA adhesive, which has a great impact on the sintering of the disc green body into porcelain. In order to prevent the PVA adhesive from volatilizing rapidly at high temperatures during the sintering process, causing cracks in the ceramic, the disc blank needs to be placed in a muffle furnace for debinding. First, the formed disc blank is placed on a corundum plate, and then placed in a muffle furnace for debinding. The debinding process in step (3) includes the following four stages:

[0022] The first stage is to raise the temperature from room temperature to 120°C and keep it for 60 min;

[0023] The second stage is to increase the temperature from 120°C to 500°C and keep it for 120 min;

[0024] The third stage is to increase the temperature from 500°C to 550°C and keep it at that temperature for 120 min;

[0025] The fourth stage is to increase the temperature from 550°C to 850°C and keep it at that temperature for 120 min, and then cool it naturally to room temperature.

[0026] Furthermore, in order to improve the density of the ceramic and enhance its mechanical strength, the debinding treated disc blank needs to be placed in a muffle furnace for sintering again. In order to prevent the sintered ceramic from sticking together and being difficult to separate, before sintering in step (4), the blank is arranged in a stacked petal form, the sintering temperature is 1400℃~1430℃, and the temperature is kept for 180min.

[0027] Furthermore, the disc ceramic material obtained after sintering does not have conductive functionality. In order to facilitate subsequent electrical testing and device applications, it needs to be electrically polarized. Before polarization, silver paste needs to be applied to the surface of the product to form an electrode.

[0028] The silver-plated polarization treatment method in step (5) is as follows: before silver-plating the ceramic, the upper and lower surfaces of the sintered ceramic material need to be polished first, and then the silver paste is evenly brushed on the smooth ceramic surface with a brush; then the ceramic piece is placed in a muffle furnace to solidify the electrode at a temperature of 550°C-650°C for 30min-60min. Finally, the ceramic disc with the electrode is placed in a polarization device for polarization treatment. The polarization voltage is 2kV-3kV, and the pressure is maintained for 3min-10min, and finally a lead-free piezoelectric ceramic material that meets performance testing and engineering requirements is obtained.

[0029] In the third aspect, the present application provides an application of a barium titanate-based lead-free piezoelectric ceramic material, which is prepared by the above-mentioned preparation method, including application in a new generation of high-precision ultra-intelligent devices with multifunctionality or other new intelligent electronic industries, such as piezoelectric / ferroelectric sensors, drivers or transducers, smart devices or intelligent electronic devices.

[0030] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0031] (1) The barium titanate-based lead-free piezoelectric ceramic material of the present invention has a unique structural feature: BSTS prepared by chemical doping strategy x After the introduction of Sn ions, the multiple local lattice distortions and polarization disorder of lead-free piezoelectric ceramics are enhanced, inducing a polar slush domain structure with extremely flat free energy. It exhibits excellent dynamic characteristics under the action of an external field and can promote the improvement of electrical performance.

[0032] (2) The barium titanate-based lead-free piezoelectric ceramic material of the present invention has excellent piezoelectric properties: BSTS prepared by chemical doping strategy x Lead-free piezoelectric ceramics, when the Sn doping content is x = 0.08, obtain excellent piezoelectric constant d 33 =820pC / N, which is more than 4 times that of pure BT lead-free piezoelectric ceramics. The improvement of piezoelectric performance helps BT-based piezoelectric ceramic materials to be used in piezoelectric devices with high sensitivity, light weight, and miniaturization.

[0033] (3) The barium titanate-based lead-free piezoelectric ceramic material of the present invention has excellent electrostrictive properties: BSTS prepared by chemical doping strategy x Lead-free piezoelectric ceramics, when the Sn doping content is x = 0.08, obtain an excellent electrostrictive coefficient Q 33 =0.045m 4 / C 2 The excellent hysteresis-striction performance helps BT-based piezoelectric ceramics to be used in high-precision displacement or strain control sensor devices.

[0034] (4) The barium titanate-based lead-free piezoelectric ceramic material of the present invention has excellent low-field near-room temperature electrocaloric performance: BSTS prepared by chemical doping strategy x Lead-free piezoelectric ceramics, when the Sn doping content is x = 0.08, have excellent low-field near-room temperature electrocaloric effect (ΔT = 0.822K, E = 30kV / cm) and huge electrocaloric strength (ΔT / ΔE = 0.425K·mm / kV). The excellent electrocaloric performance helps BT-based piezoelectric ceramics to be widely used in environmentally friendly refrigerator refrigeration or other cooling systems.

[0035] (5) The barium titanate-based lead-free piezoelectric ceramic material of the present invention has excellent mechanical properties: BSTS prepared by chemical doping strategy x Lead-free piezoelectric ceramics, when the Sn doping content is x = 0.08, have excellent resistance to plastic deformation and excellent mechanical hardness (H v =6.15GPa). The excellent mechanical behavior enables the BT-based piezoelectric ceramic material to maintain its structural integrity and stability when disturbed by external forces, so that it can effectively resist the influence of various working environments, thereby improving the service reliability of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0037] Figure 1 BSTS in the embodiment of the present invention x Technology Roadmap and BSTS for Lead-free Piezoelectric Ceramics x Domain structure morphology of lead-free piezoelectric ceramic system; (a) is the technology roadmap, (b) is the domain structure morphology; (c) is BSTS x The electrical and mechanical properties of lead-free piezoelectric ceramic systems;

[0038] Figure 2 BSTS in the embodiment of the present invention x Phase structure and microstructure of lead-free piezoelectric ceramics; (a) is BSTS x Dielectric temperature spectrum of lead-free piezoelectric ceramics; (b) BSTS x Phase diagram of lead-free piezoelectric ceramics; (c) SEM microstructure diagram and EDS spectrum analysis diagram of BSTS-0.08 ceramics; (d) HRTEM diagram and Fourier change diffraction information diagram of BSTS-0.08 ceramics;

[0039] Figure 3 BSTS in the embodiment of the present invention x Dispersive phase transition behavior diagram of lead-free piezoelectric ceramics; (a) is x = 0; (b) is x = 0.02; (c) is x = 0.04; (d) is x = 0.06; (e) is x = 0.08; (f) is x = 0.1;

[0040] Figure 4 BSTS in the embodiment of the present invention xFerroelectric and piezoelectric behavior diagram of lead-free piezoelectric ceramics; (a) is BSTS x Ferroelectric behavior of lead-free piezoelectric ceramics at different Sn doping contents; (b) BSTS x Piezoelectric behavior of lead-free piezoelectric ceramics at different Sn doping contents;

[0041] Figure 5 BSTS in the embodiment of the present invention x Electrostrictive behavior diagram of lead-free piezoelectric ceramics; (a) is x = 0; (b) is x = 0.02; (c) is x = 0.04; (d) is x = 0.06; (e) is x = 0.08; (f) is x = 0.1;

[0042] Figure 6 BSTS in the embodiment of the present invention x Electrocaloric coefficient diagram of lead-free piezoelectric ceramics; (a) is x = 0; (b) is x = 0.02; (c) is x = 0.04; (d) is x = 0.06; (e) is x = 0.08; (f) is x = 0.1;

[0043] Figure 7 BSTS in the embodiment of the present invention x Electrocaloric strength diagram of lead-free piezoelectric ceramics; (a) is x=0; (b) is x=0.02; (c) is x=0.04; (d) is x=0.06; (e) is x=0.08; (f) is x=0.1;

[0044] Figure 8 Graphs showing the plastic deformation and mechanical properties of the BSTS-0.08 lead-free piezoelectric ceramics in an embodiment of the present invention; wherein (a) is the load-displacement curve of the BSTS-0.08 lead-free piezoelectric ceramics under different nanoindentation loading conditions; (b) is the relationship between the load and hardness of the BSTS-0.08 lead-free piezoelectric ceramics; (c) is the plastic deformation behavior of the BSTS-0.08 lead-free piezoelectric ceramics under a nanoindentation load of 50 mN; and (d) is the Vickers indentation morphology graph of the BSTS-0.08 lead-free piezoelectric ceramics. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.

[0046] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] The present invention uses the "chemical doping" strategy to successfully construct a multiphase boundary structure by adding Sr and Sn in a certain formula ratio to pure BT lead-free piezoelectric ceramics, and enhance the multiple local lattice distortions and polarization disorder in the ceramic material, inducing a polar slush domain structure. This special structural feature has extremely flat free energy and exhibits excellent kinetic characteristics under the action of an external field, providing a good ion-controlled doping strategy for the development of new BT lead-free piezoelectric ceramic materials with multiple excellent properties. By adjusting the Sn ion concentration, at the x=0.08 component, BSTS x Lead-free piezoelectric ceramics also achieve excellent piezoelectric properties 33 =820pC / N, excellent hysteresis-scaling performance Q 33 =0.045m 4 / C 2 , excellent near-room temperature electrocaloric performance under small electric field (ΔT=0.822K, ΔT / ΔE=0.425K·mm / kV) and ultra-high mechanical properties (H V =6.15GPa). These performance indicators far exceed the electrical and mechanical properties of pure BT lead-free piezoelectric ceramics, and are also better than other multifunctional BT-based lead-free piezoelectric ceramic materials reported so far. The BT-based lead-free piezoelectric ceramics of the present invention have both excellent electrical properties and ultra-high mechanical properties, and are expected to be applied to a new generation of high-precision ultra-intelligent devices with multifunctionality or other new intelligent electronic industries, making important contributions to the development of electronic information intelligent technology and human progress in the new era. BSTS under each component x The specific implementation cases of lead-free piezoelectric ceramics are as follows:

[0048] Example 1

[0049] This embodiment provides a method for preparing a BSTS-0.00 lead-free piezoelectric ceramic material. The preparation process is as follows: Figure 1 As shown, follow these steps:

[0050] S1. Prepare chemical reagents: BaCO3 (AR 99%), TiO2 (AR 98%) and SrCO3 (AR 99%).

[0051] S2, the chemical reagents in step S1 are mixed according to the stoichiometric formula Ba 0.9 Sr 0.1TiO3 (BSTS-0.00) was weighed and proportioned on a high-precision balance, and then the mixture was placed in a polytetrafluoroethylene ball milling jar, and then anhydrous ethanol was added, and the mixture was placed in a rolling ball mill for 24 hours to allow the chemical reagents to be fully mixed.

[0052] S3. After the ball milling is completed, pour the BSTS-0.00 slurry into a clean basin, and then place it under a baking lamp to dry the alcohol. In the process of pouring out the evenly mixed slurry after ball milling, the ball mill should be rinsed with anhydrous ethanol several times to recover the residual slurry into the basin. Finally, pour the dried powder into the crucible and compact it, and then put it into the muffle furnace for pre-sintering at a pre-sintering temperature of 1200℃ for 120 minutes. Finally, through the solid phase reaction process of pre-sintering, a solid solution compound with a specific structure and a BSTS-0.00 ceramic main crystal are formed.

[0053] S4. Put the pre-burned BSTS-0.00 powder compound into a mortar and further grind the powder with a grinding rod. Then, add 7% to 8%wt concentration of polyvinyl alcohol (PVA) adhesive to the ground powder for grinding and granulation. After grinding out the flocs, use a microwave oven to evaporate the water in the powder compound; then, grind the powder compound into fine particles with uniform particle size again, then add an appropriate amount of PVA adhesive to grind out the flocs, and finally use a microwave oven to evaporate the water and grind it to form a granular powder compound. Subsequently, the BSTS-0.00 powder after granulation is loaded into the mold according to the required amount for compression molding. The molding instrument uses a powder molding tablet press with a molding pressure of 10MPa, and finally a disc blank with a diameter of 10mm and a height of 1.0mm is obtained.

[0054] S5. Place the formed BSTS-0.00 disc blank in a muffle furnace for debinding treatment. The temperature of the muffle furnace for debinding is set as follows: from room temperature to 120°C (keep warm for 60 minutes), then to 500°C (keep warm for 120 minutes), then to 550°C (keep warm for 120 minutes), and finally to 850°C (keep warm for 120 minutes), and then cool to room temperature with the furnace. In order to improve the density of the ceramic and enhance its mechanical strength, the disc blank after debinding treatment needs to be placed in the muffle furnace again for sintering treatment. In order to prevent the sintered ceramics from sticking together and being difficult to separate, before sintering, the blanks can be arranged in the form of stacked petals, and the sintering temperature is set to 1430°C (keep warm for 180 minutes), and then cooled to room temperature with the furnace, and finally a BSTS-0.00 ceramic disc sample is obtained.

[0055] S6. Polish the upper and lower surfaces of the sintered BSTS-0.00 ceramic material, and then use a brush to evenly brush the silver paste on the smooth ceramic surface. Finally, put the ceramic sheet into a muffle furnace to solidify the electrode at a temperature of 600°C for 30 minutes. Finally, put the BSTS-0.00 ceramic disc with the electrode into the polarization equipment for polarization treatment. The polarization voltage is 3kV, and the pressure is maintained for 10 minutes. Finally, the BSTS-0.00 lead-free piezoelectric ceramic material that meets the performance test and engineering requirements is obtained.

[0056] The following performance characteristics were performed on the BSTS-0.00 lead-free piezoelectric ceramic material prepared by the method of this embodiment.

[0057] 1) Using a variable temperature dielectric instrument to test BSTS-0.00 ceramics, the ferroelectric phase structure characteristics were confirmed ( Figure 2 ), and the main phase at room temperature is T phase. By linearly fitting the Curie-Weiss curve data points, the diffusion coefficient γ = 1.21 ( Figure 3 ), which belongs to the normal ferroelectric phase.

[0058] 2) Through the ferroelectric analyzer and d 33 The measuring instrument tested the ferroelectric and piezoelectric properties of BSTS-0.00 ceramics and obtained better ferroelectric parameters and smaller piezoelectric coefficient (d 33 =250pC / N)( Figure 4 ).

[0059] 3) The relationship between ferroelectric strain and polarization intensity is obtained by using a ferroelectric analyzer, and the relationship between ferroelectric strain and polarization intensity is fitted by a quadratic polynomial to obtain the electrostrictive coefficient Q of BSTS-0.00 ceramics 33 =0.0426m 4 / C 2 ( Figure 5 ).

[0060] 4) The relationship between polarization intensity, applied electric field and temperature was obtained using a ferroelectric analyzer, and then the relationship between the electrocaloric coefficient of BSTS-0.00 ceramics and the change between electrocaloric strength and temperature was obtained. BSTS-0.00 ceramics have a high electrocaloric coefficient ΔT = 1.416K and electrocaloric strength ΔT / ΔE = 1.195K·mm / kV at high temperatures, but the electrocaloric performance near room temperature is average ( Figure 6 ,7).

[0061] Example 2

[0062] This embodiment provides a method for preparing a BSTS-0.02 lead-free piezoelectric ceramic material. The preparation process is as follows: Figure 1 As shown, follow these steps:

[0063] S1. Prepare chemical reagents: BaCO3 (AR 99%), TiO2 (AR 98%), SrCO3 (AR 99%) and SnO2 (AR 99.5%).

[0064] S2, the above experimental materials are mixed according to the chemical stoichiometric formula Ba 0.9 Sr 0.1 Ti 0.98 Sn 0.02 O3 (BSTS-0.02) was weighed and proportioned on a high-precision balance, and then the mixture was placed in a polytetrafluoroethylene ball milling jar, and then anhydrous ethanol was added, and the mixture was placed in a rolling ball mill for 24 hours to ensure that the chemical reagents were fully mixed.

[0065] S3. After the ball milling is completed, pour the BSTS-0.02 slurry into a clean basin, and then place it under a baking lamp to dry the alcohol. In the process of pouring out the evenly mixed slurry after ball milling, the ball mill should be rinsed with anhydrous ethanol several times to recover the residual slurry into the basin. Finally, pour the dried powder into the crucible and compact it, and then put it into the muffle furnace for pre-sintering at a pre-sintering temperature of 1200℃ for 120 minutes. Finally, through the solid phase reaction process of pre-sintering, a solid solution compound with a specific structure and a BSTS-0.02 ceramic main crystal are formed.

[0066] S4. Put the pre-burned BSTS-0.02 powder compound into a mortar and further grind the powder with a grinding rod. Then, add 7% to 8%wt concentration of polyvinyl alcohol (PVA) adhesive to the ground powder for grinding and granulation. After grinding out the flocs, use a microwave oven to evaporate the water in the powder compound; then, grind the powder compound into fine particles with uniform particle size again, then add an appropriate amount of PVA adhesive to grind out the flocs, and finally use a microwave oven to evaporate the water and grind to form a granular powder compound. Subsequently, the BSTS-0.02 powder after granulation is loaded into the mold according to the required amount for compression molding. The molding instrument uses a powder molding tablet press with a molding pressure of 10MPa, and finally a disc blank with a diameter of 10mm and a height of 1.0mm is obtained.

[0067] S5. Place the formed BSTS-0.02 disc blank in a muffle furnace for debinding treatment. The temperature of the muffle furnace for debinding is set as follows: from room temperature to 120°C (keep warm for 60 minutes), then to 500°C (keep warm for 120 minutes), then to 550°C (keep warm for 120 minutes), and finally to 850°C (keep warm for 120 minutes), and then cool to room temperature with the furnace. In order to improve the density of the ceramic and enhance its mechanical strength, the disc blank after debinding treatment needs to be placed in the muffle furnace again for sintering treatment. In order to prevent the sintered ceramics from sticking together and being difficult to separate, before sintering, the blanks can be arranged in the form of stacked petals, and the sintering temperature is set to 1430°C (keep warm for 180 minutes), and then cooled to room temperature with the furnace, and finally a BSTS-0.02 ceramic disc sample is obtained.

[0068] S6. Polish the upper and lower surfaces of the sintered BSTS-0.02 ceramic material, and then use a brush to evenly brush the silver paste on the smooth ceramic surface. Finally, put the ceramic sheet into a muffle furnace to solidify the electrode at a temperature of 600°C for 30 minutes. Finally, put the BSTS-0.02 ceramic disc with the electrode into the polarization equipment for polarization treatment. The polarization voltage is 3kV, and the pressure is maintained for 10 minutes. Finally, the BSTS-0.02 lead-free piezoelectric ceramic material that meets the performance test and engineering requirements is obtained.

[0069] The following performance characteristics were performed on the BSTS-0.02 lead-free piezoelectric ceramic material prepared by the method of this embodiment.

[0070] 1) Using a variable temperature dielectric instrument to test BSTS-0.02 ceramics, the ferroelectric phase structure characteristics were confirmed ( Figure 2 ), and the T phase exists mainly at room temperature. By linearly fitting the Curie-Weiss curve data points, the diffusion coefficient γ = 1.23 ( Figure 3 ), which belongs to the normal ferroelectric phase.

[0071] 2) Through the ferroelectric analyzer and d 33 The measuring instrument tested the ferroelectric and piezoelectric properties of BSTS-0.02 ceramics and obtained better ferroelectric parameters and smaller piezoelectric coefficient (d 33 =290pC / N)( Figure 4 ).

[0072] 3) The relationship between ferroelectric strain and polarization intensity is obtained using a ferroelectric analyzer, and the relationship between ferroelectric strain and polarization intensity is fitted using a quadratic polynomial to obtain the electrostrictive coefficient Q of BSTS-0.02 ceramics 33 =0.04537m 4 / C 2 ( Figure 5 ).

[0073] 4) The relationship between polarization intensity, applied electric field and temperature was obtained using a ferroelectric analyzer, and then the relationship between the electrocaloric coefficient of BSTS-0.02 ceramics and the change between electrocaloric strength and temperature was obtained. BSTS-0.02 ceramics have a high electrocaloric coefficient ΔT = 1.059K and electrocaloric strength ΔT / ΔE = 0.894K·mm / kV at high temperatures, but the electrocaloric performance near room temperature is average ( Figure 6 ,7).

[0074] Example 3

[0075] This embodiment provides a method for preparing a BSTS-0.04 lead-free piezoelectric ceramic material. The preparation process is as follows: Figure 1 As shown, follow these steps:

[0076] S1. Prepare chemical reagents: BaCO3 (AR 99%), TiO2 (AR 98%), SrCO3 (AR 99%) and SnO2 (AR 99.5%).

[0077] S2, the above experimental materials are mixed according to the chemical stoichiometric formula Ba 0.9 Sr 0.1 Ti 0.96 Sn 0.04 O3 (BSTS-0.04) was weighed and proportioned on a high-precision balance, and then the mixture was placed in a polytetrafluoroethylene ball milling jar, and then anhydrous ethanol was added, and the mixture was placed in a rolling ball mill for 24 hours to ensure that the chemical reagents were fully mixed.

[0078] S3. After the ball milling is completed, pour the BSTS-0.04 slurry into a clean basin, and then place it under a baking lamp to dry the alcohol. In the process of pouring out the evenly mixed slurry after ball milling, the ball mill should be rinsed with anhydrous ethanol several times to recover the residual slurry into the basin. Finally, pour the dried powder into the crucible and compact it, and then put it into the muffle furnace for pre-sintering at a pre-sintering temperature of 1200℃ for 120 minutes. Finally, through the solid phase reaction process of pre-sintering, a solid solution compound with a specific structure and a BSTS-0.04 ceramic main crystal are formed.

[0079] S4. Put the pre-burned BSTS-0.04 powder compound into a mortar and further grind the powder with a grinding rod. Then, add 7% to 8%wt concentration of polyvinyl alcohol (PVA) adhesive to the ground powder for grinding and granulation. After grinding out the flocs, use a microwave oven to evaporate the water in the powder compound; then, grind the powder compound into fine particles with uniform particle size again, then add an appropriate amount of PVA adhesive to grind out the flocs, and finally use a microwave oven to evaporate the water and grind to form a granular powder compound. Subsequently, the BSTS-0.04 powder after granulation is loaded into the mold according to the required amount for compression molding. The molding instrument uses a powder molding tablet press with a molding pressure of 10MPa, and finally a disc blank with a diameter of 10mm and a height of 1.0mm is obtained.

[0080] S5. Place the formed BSTS-0.04 disc blank in a muffle furnace for debinding treatment. The temperature of the muffle furnace for debinding is set as follows: from room temperature to 120°C (60 minutes of heat preservation), then to 500°C (120 minutes of heat preservation), then to 550°C (120 minutes of heat preservation), and finally to 850°C (120 minutes of heat preservation), and then cool to room temperature with the furnace. In order to improve the density of the ceramic and enhance its mechanical strength, the disc blank after debinding treatment needs to be placed in the muffle furnace again for sintering treatment. In order to prevent the sintered ceramics from sticking together and being difficult to separate, before sintering, the blanks can be arranged in the form of stacked petals, and the sintering temperature is set to 1430°C (180 minutes of heat preservation), and then cooled to room temperature with the furnace, and finally a BSTS-0.04 ceramic disc sample is obtained.

[0081] S6. Polish the upper and lower surfaces of the sintered BSTS-0.04 ceramic material, and then use a brush to evenly brush the silver paste on the smooth ceramic surface. Finally, put the ceramic sheet into a muffle furnace to solidify the electrode at a temperature of 600°C for 30 minutes. Finally, put the BSTS-0.04 ceramic disc with electrodes into a polarization device for polarization treatment. The polarization voltage is 3kV, and the pressure is maintained for 10 minutes. Finally, the BSTS-0.04 lead-free piezoelectric ceramic material that meets performance testing and engineering requirements is obtained.

[0082] The following performance characteristics were performed on the BSTS-0.04 lead-free piezoelectric ceramic material prepared by the method of this embodiment.

[0083] 1) Using a variable temperature dielectric instrument to test BSTS-0.04 ceramics, the ferroelectric phase structure characteristics were confirmed ( Figure 2 ), and exists as an OT phase boundary at room temperature. By linearly fitting the Curie-Weiss curve data points, the diffusion coefficient γ = 1.36 ( Figure 3 ), which belongs to the normal ferroelectric phase.

[0084] 2) Through the ferroelectric analyzer and d 33 The measuring instrument tested the ferroelectric and piezoelectric properties of BSTS-0.04 ceramics and obtained good ferroelectric parameters and good piezoelectric coefficient (d 33 =478pC / N)( Figure 4 ).

[0085] 3) The relationship between ferroelectric strain and polarization intensity is obtained using a ferroelectric analyzer, and the relationship between ferroelectric strain and polarization intensity is fitted using a quadratic polynomial to obtain the electrostrictive coefficient Q of BSTS-0.04 ceramics 33 =0.04574m 4 / C 2 ( Figure 5 ).

[0086] 4) The relationship between polarization intensity, applied electric field and temperature was obtained using a ferroelectric analyzer, and then the relationship between the electrocaloric coefficient of BSTS-0.04 ceramics and the change between electrocaloric strength and temperature was obtained. BSTS-0.04 ceramics have a higher electrocaloric coefficient ΔT = 0.905K and electrocaloric strength ΔT / ΔE = 0.644K·mm / kV at higher temperatures, but the electrocaloric performance near room temperature is average ( Figure 6 ,7).

[0087] Example 4

[0088] This embodiment provides a method for preparing a BSTS-0.06 lead-free piezoelectric ceramic material. The preparation process is as follows: Figure 1 As shown, follow these steps:

[0089] S1. Prepare chemical reagents: BaCO3 (AR 99%), TiO2 (AR 98%), SrCO3 (AR 99%) and SnO2 (AR 99.5%).

[0090] S2, the above experimental materials are mixed according to the chemical stoichiometric formula Ba 0.9 Sr 0.1 Ti 0.94 Sn 0.06 O3 (BSTS-0.06) was weighed and proportioned on a high-precision balance, and then the mixture was placed in a polytetrafluoroethylene ball milling jar, and then anhydrous ethanol was added, and the mixture was placed in a rolling ball mill for 24 hours to ensure that the chemical reagents were fully mixed.

[0091] S3. After the ball milling is completed, pour the BSTS-0.06 slurry into a clean basin, and then place it under a baking lamp to dry the alcohol. In the process of pouring out the evenly mixed slurry after ball milling, the ball mill should be rinsed with anhydrous ethanol several times to recover the residual slurry into the basin. Finally, pour the dried powder into the crucible and compact it, and then put it into the muffle furnace for pre-sintering at a pre-sintering temperature of 1200℃ for 120 minutes. Finally, through the solid phase reaction process of pre-sintering, a solid solution compound with a specific structure and a BSTS-0.06 ceramic main crystal are formed.

[0092] S4. Put the pre-burned BSTS-0.06 powder compound into a mortar and further grind the powder with a grinding rod. Then, add 7% to 8%wt concentration of polyvinyl alcohol (PVA) adhesive to the ground powder for grinding and granulation. After grinding out the flocs, use a microwave oven to evaporate the moisture in the powder compound; then, grind the powder compound into fine particles with uniform particle size again, then add an appropriate amount of PVA adhesive to grind out the flocs, and finally use a microwave oven to evaporate the moisture and grind to form a granular powder compound. Subsequently, the BSTS-0.06 powder after granulation is loaded into the mold according to the required amount for compression molding. The molding instrument uses a powder molding tablet press with a molding pressure of 10MPa, and finally a disc blank with a diameter of 10mm and a height of 1.0mm is obtained.

[0093] S5. Place the formed BSTS-0.06 disc blank in a muffle furnace for debinding treatment. The temperature of the muffle furnace for debinding is set as follows: from room temperature to 120°C (keep warm for 60 minutes), then to 500°C (keep warm for 120 minutes), then to 550°C (keep warm for 120 minutes), and finally to 850°C (keep warm for 120 minutes), and then cool to room temperature with the furnace. In order to improve the density of the ceramic and enhance its mechanical strength, the disc blank after debinding treatment needs to be placed in the muffle furnace again for sintering treatment. In order to prevent the sintered ceramics from sticking together and being difficult to separate, before sintering, the blanks can be arranged in the form of stacked petals, and the sintering temperature is set to 1430°C (keep warm for 180 minutes), and then cooled to room temperature with the furnace, and finally a BSTS-0.06 ceramic disc sample is obtained.

[0094] S6. Polish the upper and lower surfaces of the sintered BSTS-0.06 ceramic material, and then use a brush to evenly brush the silver paste on the smooth ceramic surface. Finally, put the ceramic sheet into a muffle furnace to solidify the electrode at a temperature of 600°C for 30 minutes. Finally, put the BSTS-0.06 ceramic disc with electrodes into a polarization device for polarization treatment. The polarization voltage is 3kV, and the pressure is maintained for 10 minutes. Finally, the BSTS-0.06 lead-free piezoelectric ceramic material that meets performance testing and engineering requirements is obtained.

[0095] The following performance characteristics were performed on the BSTS-0.06 lead-free piezoelectric ceramic material prepared by the method of this embodiment.

[0096] 1) Using a variable temperature dielectric instrument to test BSTS-0.06 ceramics, the ferroelectric phase structure characteristics were confirmed ( Figure 2 ), and it exists as an OT phase boundary at room temperature. By linearly fitting the Curie-Weiss curve data points, the diffusion coefficient γ=1.39( Figure 3 ), which belongs to the normal ferroelectric phase.

[0097] 2) Through the ferroelectric analyzer and d 33 The measuring instrument tested the ferroelectric and piezoelectric properties of BSTS-0.06 ceramics and obtained good ferroelectric parameters and good piezoelectric coefficients (d 33 =660pC / N)( Figure 4 ).

[0098] 3) The relationship between ferroelectric strain and polarization intensity was obtained using a ferroelectric analyzer, and the relationship between ferroelectric strain and polarization intensity was fitted using a quadratic polynomial to obtain the electrostrictive coefficient Q of BSTS-0.06 ceramics. 33 =0.041m 4 / C 2 ( Figure 5 ).

[0099] 4) The relationship between polarization intensity, applied electric field and temperature was obtained using a ferroelectric analyzer, and then the relationship between the electrocaloric coefficient of BSTS-0.06 ceramics and the change between electrocaloric strength and temperature was obtained. BSTS-0.06 ceramics have a higher electrocaloric coefficient ΔT = 0.947K and electrocaloric strength ΔT / ΔE = 0.552K·mm / kV at higher temperatures, but the electrocaloric performance near room temperature is average ( Figure 6 ,7).

[0100] Example 5

[0101] This embodiment provides a method for preparing a BSTS-0.08 lead-free piezoelectric ceramic material. The preparation process is as follows: Figure 1 As shown, follow these steps:

[0102] S1. Prepare chemical reagents: BaCO3 (AR 99%), TiO2 (AR 98%), SrCO3 (AR 99%) and SnO2 (AR 99.5%).

[0103] S2, the above experimental materials are mixed according to the chemical stoichiometric formula Ba 0.9 Sr 0.1 Ti 0.92 Sn 0.08O3 (BSTS-0.08) was weighed and proportioned on a high-precision balance, and then the mixture was placed in a polytetrafluoroethylene ball milling jar, and then anhydrous ethanol was added, and the mixture was placed in a rolling ball mill for 24 hours to ensure that the chemical reagents were fully mixed.

[0104] S3. After the ball milling is completed, pour the BSTS-0.08 slurry into a clean basin, and then place it under a baking lamp to dry the alcohol. In the process of pouring out the evenly mixed slurry after ball milling, the ball mill should be rinsed with anhydrous ethanol several times to recover the residual slurry into the basin. Finally, pour the dried powder into the crucible and compact it, and then put it into the muffle furnace for pre-sintering at a pre-sintering temperature of 1200°C for 120 minutes. Finally, through the solid phase reaction process of pre-sintering, a solid solution compound with a specific structure and a BSTS-0.08 ceramic main crystal are formed.

[0105] S4. Put the pre-burned BSTS-0.08 powder compound into a mortar and further grind the powder with a grinding rod. Then, add 7% to 8%wt concentration of polyvinyl alcohol (PVA) adhesive to the ground powder for grinding and granulation. After grinding out the flocs, use a microwave oven to evaporate the water in the powder compound; then, grind the powder compound into fine particles with uniform particle size again, then add an appropriate amount of PVA adhesive to grind out the flocs, and finally use a microwave oven to evaporate the water and grind it to form a granular powder compound. Subsequently, the BSTS-0.08 powder after granulation is loaded into the mold according to the required amount for compression molding. The molding instrument uses a powder molding tablet press with a molding pressure of 10MPa, and finally a disc blank with a diameter of 10mm and a height of 1.0mm is obtained.

[0106] S5. Place the formed BSTS-0.08 disc blank in a muffle furnace for debinding treatment. The temperature of the muffle furnace for debinding is set as follows: from room temperature to 120°C (keep warm for 60 minutes), then to 500°C (keep warm for 120 minutes), then to 550°C (keep warm for 120 minutes), and finally to 850°C (keep warm for 120 minutes), and then cool to room temperature with the furnace. In order to improve the density of the ceramic and enhance its mechanical strength, the disc blank after debinding treatment needs to be placed in the muffle furnace again for sintering treatment. In order to prevent the sintered ceramics from sticking together and being difficult to separate, the blanks can be arranged in the form of stacked petals before sintering. The sintering temperature is set to 1430°C (keep warm for 180 minutes), and then cooled to room temperature with the furnace, and finally a BSTS-0.08 ceramic disc sample is obtained.

[0107] S6. Polish the upper and lower surfaces of the sintered BSTS-0.08 ceramic material, and then use a brush to evenly brush the silver paste on the smooth ceramic surface. Finally, put the ceramic sheet into a muffle furnace to solidify the electrode at a temperature of 600°C for 30 minutes. Finally, put the BSTS-0.08 ceramic disc with electrodes into a polarization device for polarization treatment. The polarization voltage is 3kV, and the pressure is maintained for 10 minutes. Finally, the BSTS-0.08 lead-free piezoelectric ceramic material that meets performance testing and engineering requirements is obtained.

[0108] The following performance characteristics were performed on the BSTS-0.08 lead-free piezoelectric ceramic material prepared by the method of this embodiment.

[0109] 1) Using a variable temperature dielectric instrument to test BSTS-0.08 ceramics, the ferroelectric phase structure characteristics were confirmed ( Figure 2 ), at room temperature, the OT phase boundary exists mainly, and the RO phase boundary and the TC phase boundary are also close to room temperature, so it can be considered as a ROTC coexistence structure. At this time, there are enhanced multiple local lattice distortions and polarization disorder, which can induce polar slush domain structure ( Figure 1 ), has extremely flat free energy, shows excellent dynamic characteristics under the action of external field, and can promote the improvement of electrical performance. By observing its microstructure through SEM, we can see the dense grain structure. Using energy dispersive spectrometer (EDS) to analyze its element distribution, we found that each element is evenly distributed in the ceramic ( Figure 2 ). HRTEM is used to obtain the atomic distribution information and electron diffraction spectrum of the ceramic. It can be found that the atoms of the ceramic material are arranged neatly without defects or dislocations, indicating that it has high-quality crystallinity ( Figure 2 ).

[0110] Among them, when the Sn content is 0.08, the phase boundary temperatures are T R-O =8℃、T O-T =23℃ and T T-C =41°C. At this point, it is a complex multi-phase coexistence structure with flat free energy and excellent electrical properties.

[0111] 2) The dielectric-temperature spectrum of BSTS-0.08 ceramics was obtained by dielectric instrument. The diffusion coefficient of BSTS-0.08 ceramics was obtained by linear fitting of the Curie-Weiss curve data points. Figure 3 ), has a certain degree of dispersion, but is a normal ferroelectric.

[0112] 3) Through the ferroelectric analyzer and d 33 The measuring instrument tested the ferroelectric and piezoelectric properties of BSTS-0.08 ceramics and obtained good ferroelectric parameters and the best piezoelectric coefficient (d 33=820pC / N)( Figure 4 ).

[0113] 4) The relationship between ferroelectric strain and polarization intensity was obtained using a ferroelectric analyzer, and the relationship between ferroelectric strain and polarization intensity was fitted using a quadratic polynomial to obtain the electrostrictive coefficient Q of BSTS-0.08 ceramics. 33 =0.045m 4 / C 2 ( Figure 5 ).

[0114] 5) The relationship between polarization intensity, applied electric field and temperature was obtained using a ferroelectric analyzer, and then the relationship between the electrocaloric coefficient of BSTS-0.08 ceramic and the change between electrocaloric strength and temperature was obtained. BSTS-0.08 ceramic has an excellent electrocaloric coefficient ΔT = 0.822K and an ultra-high electrocaloric strength ΔT / ΔE = 0.425K·mm / kV near room temperature ( Figure 6 ,7).

[0115] 6) The load-displacement curve of BSTS-0.08 ceramic material was obtained by nanoindentation, and the plastic deformation behavior of ceramic and the indentation depth H = 250nm were obtained. At the same time, two real hardnesses related to elasticity and plasticity of BSTS-0.08 ceramic were calculated by PSR model ( Figure 8 ). In addition, the hardness H of BSTS-0.08 ceramic material was obtained by using Vickers indentation instrument. v =6.28GPa( Figure 8 ), which is consistent with the real hardness value obtained by nanoindentation. This hardness value is better than that of many lead-free piezoelectric ceramic materials, which is conducive to the stability and reliability of BSTS-0.08 lead-free piezoelectric ceramics in actual working conditions.

[0116] When the Sn content is 0.08, excellent comprehensive performance (d 33 =820pC / N,Q 33 =0.045m 4 / C 2 , ΔT=0.822K, H V =6.15GPa), these performance indicators far exceed the electrical and mechanical properties of pure BT lead-free piezoelectric ceramics, and are also better than other multifunctional BT-based lead-free piezoelectric ceramic materials reported so far. This new type of BT-based lead-free piezoelectric ceramic with multiple excellent electrical properties and ultra-high mechanical properties is expected to be used in a new generation of advanced multifunctional super-intelligent devices or other new intelligent electronic industries, making important contributions to the development of electronic information intelligent technology and human progress in the new era.

[0117] Example 6

[0118] This embodiment provides a method for preparing a BSTS-0.10 lead-free piezoelectric ceramic material. The preparation process is as follows: Figure 1 As shown, follow these steps:

[0119] S1. Prepare chemical reagents: BaCO3 (AR 99%), TiO2 (AR 98%), SrCO3 (AR 99%) and SnO2 (AR 99.5%).

[0120] S2, the above experimental materials are mixed according to the chemical stoichiometric formula Ba 0.9 Sr 0.1 Ti 0.90 Sn 0.10 O3 (BSTS-0.10) was weighed and proportioned on a high-precision balance, and then the mixture was placed in a polytetrafluoroethylene ball milling jar, and then anhydrous ethanol was added, and the mixture was placed in a rolling ball mill for 24 hours to ensure that the chemical reagents were fully mixed.

[0121] S3. After the ball milling is completed, pour the BSTS-0.10 slurry into a clean basin, and then place it under a baking lamp to dry the alcohol. In the process of pouring out the evenly mixed slurry after ball milling, the ball mill should be rinsed with anhydrous ethanol several times to recover the residual slurry into the basin. Finally, pour the dried powder into the crucible and compact it, and then put it into the muffle furnace for pre-sintering at a pre-sintering temperature of 1200℃ for 120 minutes. Finally, through the solid phase reaction process of pre-sintering, a solid solution compound with a specific structure and a BSTS-0.10 ceramic main crystal are formed.

[0122] S4. Put the pre-burned BSTS-0.10 powder compound into a mortar and further grind the powder with a grinding rod. Then, add 7% to 8%wt concentration of polyvinyl alcohol (PVA) adhesive to the ground powder for grinding and granulation. After grinding out the flocs, use a microwave oven to evaporate the water in the powder compound; then, grind the powder compound into fine particles with uniform particle size again, then add an appropriate amount of PVA adhesive to grind out the flocs, and finally use a microwave oven to evaporate the water and grind to form a granular powder compound. Subsequently, the BSTS-0.10 powder after granulation is loaded into the mold according to the required amount for compression molding. The molding instrument uses a powder molding tablet press with a molding pressure of 10MPa, and finally a disc blank with a diameter of 10mm and a height of 1.0mm is obtained.

[0123] S5. Place the formed BSTS-0.10 disc blank in a muffle furnace for debinding treatment. The temperature of the muffle furnace for debinding is set as follows: from room temperature to 120°C (keep warm for 60 minutes), then to 500°C (keep warm for 120 minutes), then to 550°C (keep warm for 120 minutes), and finally to 850°C (keep warm for 120 minutes), and then cool to room temperature with the furnace. In order to improve the density of the ceramic and enhance its mechanical strength, the disc blank after debinding treatment needs to be placed in the muffle furnace again for sintering treatment. In order to prevent the sintered ceramics from sticking together and being difficult to separate, the blanks can be arranged in the form of stacked petals before sintering. The sintering temperature is set to 1430°C (keep warm for 180 minutes), and then cooled to room temperature with the furnace, and finally a BSTS-0.10 ceramic disc sample is obtained.

[0124] S6. Polish the upper and lower surfaces of the sintered BSTS-0.10 ceramic material, and then use a brush to evenly brush the silver paste on the smooth ceramic surface. Finally, put the ceramic sheet into a muffle furnace to solidify the electrode at a temperature of 600°C for 30 minutes. Finally, put the BSTS-0.10 ceramic disc with electrodes into a polarization device for polarization treatment. The polarization voltage is 3kV, and the pressure is maintained for 10 minutes. Finally, the BSTS-0.10 lead-free piezoelectric ceramic material that meets performance testing and engineering requirements is obtained.

[0125] The following performance characteristics were performed on the BSTS-0.10 lead-free piezoelectric ceramic material prepared by the method of this embodiment.

[0126] 1) Using a variable temperature dielectric instrument to test BSTS-0.10 ceramics, the ferroelectric phase structure characteristics were confirmed ( Figure 2 ), at room temperature, the RO phase boundary, OT phase boundary and TC phase boundary merge into one point, which is a typical ROTC multiphase coexistence structure. By linearly fitting the Curie-Weiss curve data points, the diffusion coefficient γ = 1.47 ( Figure 3 ), the relaxation degree increases, and it has a certain degree of relaxation.

[0127] Combined with the detection results in the above embodiments, Figure 2 It can be seen from the figure that the dielectric properties change with the change of Sn doping content; with the increase of Sn doping content, the RO phase boundary, OT phase boundary and TC phase boundary gradually merge into one point, proving that Sn doping can effectively regulate its multiphase structure. Figure 3 It can be seen that with the increase of Sn doping content, BSTS x The dispersion degree of lead-free piezoelectric ceramics is also gradually increasing, indicating that the relaxation characteristics are becoming more and more obvious.

[0128] 2) Through the ferroelectric analyzer and d 33The measuring instrument tested the ferroelectric and piezoelectric properties of BSTS-0.10 ceramics and obtained general ferroelectric parameters and a small piezoelectric coefficient (d 33 =206pC / N)( Figure 4 ).

[0129] Combined with the test results of the above embodiments, Figure 4 It can be seen that with the increase of Sn content, the maximum polarization intensity (P max ), residual polarization intensity (P r ) and the coercive field (E c ) are reduced at the same time.

[0130] 4) The relationship between the ferroelectric strain and polarization intensity of BSTS-0.10 ceramics was obtained using a ferroelectric analyzer. The relationship between the ferroelectric strain and polarization intensity was fitted using a quadratic polynomial to obtain the electrostrictive coefficient Q of BSTS-0.10 ceramics. 33 =0.0391m 4 / C 2 ( Figure 5 ).

[0131] 5) The relationship between polarization intensity, applied electric field and temperature was obtained using a ferroelectric analyzer, and then the relationship between the electrocaloric coefficient of BSTS-0.10 ceramics and the change between electrocaloric strength and temperature was obtained. BSTS-0.10 ceramics have an excellent electrocaloric coefficient ΔT = 0.705K and a high electrocaloric strength ΔT / ΔE = 0.386K·mm / kV near room temperature ( Figure 6 ,7).

[0132] Combined with the test results of the above embodiments, Figure 6 It can be seen that different temperatures and different electric fields correspond to different electrocaloric coefficients. In the phase transition region, the electrocaloric coefficient is the largest. x Lead-free piezoelectric ceramics, when x = 0.08, have the best electrocaloric coefficient ΔT = 0.822K near room temperature, indicating that the ceramics with this component are a promising piezoelectric material that can be used in refrigeration technology. Figure 7 It can be seen that different temperatures and different electric fields correspond to different electrocaloric intensities, and the electrocaloric intensity is the largest in the phase transition region. x The lead-free piezoelectric ceramics, when x = 0.08, have the best electrocaloric strength ΔT / ΔE = 0.425K·mm / kV near room temperature, indicating that the ceramics with this composition have excellent refrigeration effect.

[0133] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A barium titanate-based lead-free piezoelectric ceramic material, characterized in that: The chemical formula of the barium titanate-based lead-free piezoelectric ceramic material is Ba 0.9 Sr 0.1 Ti 1-x Sn x O3, wherein x = 0 to 0.10, and x represents the molar fraction.

2. A method for preparing the barium titanate-based lead-free piezoelectric ceramic material according to claim 1, characterized in that: The following steps are involved: (1) weighing chemical reagents BaCO3, TiO2, SrCO3 and SnO2 according to the chemical formula of barium titanate-based lead-free piezoelectric ceramic materials to prepare powder; (2) using the powder to perform granulation molding to prepare a disc body; (3) performing a debinding process on the disc blank; (4) sintering the debinding disc green body to obtain a disc ceramic material; (5) The sintered disc ceramic material is subjected to silver plating and polarization treatment to obtain a lead-free piezoelectric ceramic material.

3. The method for preparing a barium titanate-based lead-free piezoelectric ceramic material according to claim 2, characterized in that: When preparing the powder in step (1), the weighed chemical reagents are firstly subjected to ball milling treatment, then to drying treatment, and finally to pre-calcination treatment.

4. The method for preparing a barium titanate-based lead-free piezoelectric ceramic material according to claim 3, characterized in that: The temperature during the pre-firing treatment is controlled at 1160°C to 1220°C, and the temperature is kept for 120min to 180min.

5. The method for preparing a barium titanate-based lead-free piezoelectric ceramic material according to claim 2, characterized in that: When preparing the disc body in step (2), the pre-burned powder is first ground and then added to a polyvinyl alcohol binder for grinding and granulation. The granulated powder is loaded into a mold and formed on a powder dry pressing machine.

6. The method for preparing a barium titanate-based lead-free piezoelectric ceramic material according to claim 5, characterized in that: The prepared disc blank has a diameter of 10 mm and a height of 0.8 mm to 1.5 mm.

7. The method for preparing a barium titanate-based lead-free piezoelectric ceramic material according to claim 2, characterized in that: The debinding process in step (3) includes the following four stages: The first stage is to raise the temperature from room temperature to 120°C and keep it for 60 min; The second stage is to increase the temperature from 120°C to 500°C and keep it for 120 min; The third stage is to increase the temperature from 500°C to 550°C and keep it at that temperature for 120 min; The fourth stage is to increase the temperature from 550°C to 850°C and keep it at that temperature for 120 min, and then cool it naturally to room temperature.

8. The method for preparing a barium titanate-based lead-free piezoelectric ceramic material according to claim 2, characterized in that: Before sintering in step (4), the green bodies are arranged in a stacked petal form, the sintering temperature is 1400° C. to 1430° C., and the temperature is kept for 180 minutes.

9. The method for preparing a barium titanate-based lead-free piezoelectric ceramic material according to claim 2, characterized in that: The silver-plated polarization treatment method in step (5) is as follows: first, silver paste is evenly applied on both sides of the ceramic to form a continuous silver paste film; then, the ceramic sheet coated with silver paste is heated to ensure that the silver paste is tightly bonded to the ceramic surface and provides good conductive properties; finally, the ceramic disc with electrodes is placed in a polarization device for polarization treatment to obtain a lead-free piezoelectric ceramic material.

10. Use of the barium titanate-based lead-free piezoelectric ceramic material according to claim 1 or the barium titanate-based lead-free piezoelectric ceramic material prepared by the preparation method according to any one of claims 2 to 9, characterized in that: Including applications in piezoelectric / ferroelectric sensors, drivers, transducers, smart devices or intelligent electronic devices.

Citation Information

Patent Citations

  • Doped barium titanate lead-free ceramic with high electrostrictive strain and low hysteresis and preparation method of doped barium titanate lead-free ceramic

    CN115093216A

  • Composite Bismuth-based lead-free piezoelectric ceramics and process for preparing the same

    KR101767130B1

Cited By

  • Preparation method of BST-based low-hysteresis lead-free piezoelectric ceramic system

    CN120554109A